A manualised approach to anger management in a group therapy context: striving towards accessibility, affordability and inclusivity within mainstream schools. (3rd April 2018) - Wiseman, Martin; O'Gorman, Shannon
Abstract: Queensland has recently seen the first conviction under the new one-punch law. In this instance a then 19-year-old male punched and fatally injured a 54–year-old man. This article details a six session manualised group therapy approach that was applied within a mainstream school in an effort to support adolescents who had been identified as having regular and heightened episodes of inappropriately expressed anger. The cohort of students attending this school is characterised by a diversity of cultures, families of low socio-economic means and a significant proportion of students verified as having special needs. As such, the introduction of a new therapeutic program was designed to accommodate the needs of a range of students whilst necessarily remaining alert to matters of financial viability. This manualised approach seeks to provide: a common vocabulary for application by teachers/parents/students alike; rehearsed problem solving skills; and an identifiable method to continuing the exploration of cognitions, physical/emotional responses, behavioural choices and associated values. This article will articulate the content specific to the manual such that practitioners may consider application within their own practice. Results of the impact of this manual will be described with reference to two different cohorts – each containing six male students. Group one were scored according to both the PROMIS Emotional Distress – Calibrated Anger Measure Paediatric and Personal Anger Assessment, whereas group two were scored according to the Resiliency Scales for Children and Adolescents.